The Relationship between Formal Thinking & Learning Styles for Kindergarten Department Students (Journal Of Educational and Psychological Researches, 2023)
The current research aims to reveal the strength of education and the direction of the relationship between the formal thinking and learning methods of Kindergarten department students. To achieve this objective, the researcher developed a scale of formal thinking according to the theory of (Inhelder & Piaget 1958) consisting of (25) items in the form of declarative phrases derived from the analysis of formal thinking skills based on a professional situation that students are expected to interact with in a professional way. The research sample consisted of (100) female students selected randomly who were divided into four groups based on the academic stages, the results revealed that The level of formal thinking of the main sample is moderate. The sample was distributed among learning methods in different percentages and in the following descending order (convergent 30%, adaptive 27%, divergent 24%, absorptive 19%). There is a significant difference in terms of the academic levels in favor of the fourth stage. There is a weak negative correlation between the two variables. The research came out with a set of recommendations, including holding training workshops for teachers about the importance and detecting students’ preferred learning methods